Movimentos sociais e contramovimentos: mobilizações antiaborto no Brasil contemporâneo - Rezende, Patricia Jimenez [UNIFESP] (2016)
This research brings forward the formation and the dynamics of antiabortion mobilizations as a countermovement to the movement mobilization of pro-abortion groups and to State policies. Based on the political process theory, the research focus on the sociopolitical environment formation of the countermovement (opportunities and political constraints) and the relational dynamics that was established between the repertoires of collective action and frames antiabortion and pro-abortion. In theory of political confrontation the concepts counter-mobilization and countermovement have been used to circumscribe theoretically movements formed against certain pre-existing movements. Studies in this area focus on movements that act antagonistically to the initial social movements. In the context of the election cycle of 2006 the antiabortion mobilization was presented as representative of changes in the field of political confrontation about abortion, initiated in the context of sexual and reproductive rights regulation in Brazil during the first Lula´s Government. This research presents the counter-mobilization against the abortion agenda that culminated in the Nacional Campaign in Defense of Life, over the election cycle of 2006 and, at the same time, the formation of the National Citizens Movement for Life - Brazil Without Abortion. In this conjunction, the analysis of this dissertation focuses on the national antiabortion mobilizations and your interaction with the feminist movement in the broader and relational context with the state, during the electoral confrontation of 2006.